Antimicrobial stewardship in Tanzania: a consideration of strengths, weaknesses, opportunities and challenges for maintenance and further development of efforts. Issue 3 (5th September 2016) - Eliakimu, Eliudi
Abstract : Purpose: Worldwide situation analysis on antimicrobial resistance (AMR) released in 2015 by the World Health Organisation (WHO) has revealed inadequate capability to respond to AMR in African region. Report of antibiotics use and resistance in Tanzania revealed rising levels of health-care associated Methicilin Resistant Staphylococcus aureus (MRSA) infections; while other studies have reported high prevalence of Expanded Spectrum Beta-Lactamase (ESBL). The purpose of the article is to review the current situation of antimicrobial stewardship (AMS) in Tanzania using Strengths, Weaknesses, Opportunities and Challenges (SWOC) analysis. Design/methodology/approach: General literature review was done on use of antimicrobials in Google Scholar, websites of key organisations including WHO, and grey literature. Conceptual framework designed by the author was used to inform SWOC analysis of the Tanzanian health sector. Findings: The SWOC analysis has revealed much strength in the Tanzanian health sector indicating that increasing investments in laboratory services, in medicines Regulatory Authority and Pharmacy Council, and strengthening Management Teams at all levels of service delivery, including Medicines and Therapeutics Committees (MTCs); and strengthening advocacy on rational use of antimicrobials both in humans and livestock will improve AMS. Research limitations/implications: This is a general literature review. No interview of experts or use of questionnaires was used. However, based on the literature found and author's experience in the health sector, the information contained is valid for consideration in making policy decisions about AMR in Tanzania. Practical implications: Designing policy interventions to prevent development of AMR to commonly used antimicrobials. Originality/value: This is my original idea backed by available literature.